2014
DOI: 10.1007/s11655-014-1847-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential advantages of Chinese medicine Taohong Siwu Decoction (桃红四物汤) combined with tissue-plasminogen activator for alleviating middle cerebral artery occlusion-induced embolic stroke in rats

Abstract: A combination of low-dose rt-PA and TSD after embolic stroke reduced infarct volume, improved cerebral blood flow and provided neuroprotection and these effects were associated with reduction of apoptosis and attenuation of HIF-1α, TNF-α and iNOS expression. These results provide a positive contribution to better understand the therapeutic value of the combination of TSD with rt-PA in ischemic stroke and may support further clinical evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…A wide range of benefits of THSWD have been identified since its introduction, including stimulation of blood circulation, neuroprotection, and facilitation of angiogenesis (17)(18)(19). A combination of a recombinant tissue-type plasminogen activator and THSWD resulted in a decreased infarct size, it stimulated cerebral blood circulation, and it enhanced neuron function in patients who had suffered a cerebral embolic stroke (20). THSWD has been used to treat rabbits in a model of SANFH, resulting in reduced blood viscosity, increased regeneration of local microvessels, improved local blood supply, and facilitation of the recovery of the necrotic femoral head (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of benefits of THSWD have been identified since its introduction, including stimulation of blood circulation, neuroprotection, and facilitation of angiogenesis (17)(18)(19). A combination of a recombinant tissue-type plasminogen activator and THSWD resulted in a decreased infarct size, it stimulated cerebral blood circulation, and it enhanced neuron function in patients who had suffered a cerebral embolic stroke (20). THSWD has been used to treat rabbits in a model of SANFH, resulting in reduced blood viscosity, increased regeneration of local microvessels, improved local blood supply, and facilitation of the recovery of the necrotic femoral head (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…In accordance with Yiqi Huoxue, the traditional Chinese medicines THSWD and BYD were reported to markedly improve heart function in patients with congestive heart failure in conjunction with conventional therapy (20,21). Experimental studies confirmed that THSWD can inhibit proliferation of myocardium interstitial collagenous fibers and expression of collagen protein after acute myocardial infarction (MI) in rats (22), decrease hepatic necroinflammatory disease and fibrosis in an animal model of chronic liver disease (23), and inhibit inflammatory responses by decreasing the expression of TNF-α in cerebral ischemia (24). Both Zhang et al and Du et al found that cardioprotection conferred by BYD was related to attenuation of oxidative stress and inflammatory cell infiltration in CHF post-MI induced by ligation of the left anterior descending (LAD) artery (25,26).…”
Section: Introductionmentioning
confidence: 93%
“…Similarly, ShenGui SanSheng san could also improve the efficiency of citric acid cycle to improve the brain energy deficit after ischemia (Luo et al, 2019). Interestingly, as a cell-sensing oxygen sensor, most studies have also reported evidence of other TCM prescriptions regulating HIF-1a to inhibit apoptosis and inflammation in treatment of stroke, such as XueFu ZhuYu decoction (Lee et al, 2011) and TaoHong SiWu decoction (Yen et al, 2014). Members of the Bcl-2 family are also potential targets for prescription inhibition of apoptosis to improve ischemic brain injury.…”
Section: Prescription and Molecular Mechanisms In Regulating Mptp Opementioning
confidence: 99%